Introduction to plant physiology - Hopkins, William G.; Hopkins, William G.; Huner, Norman P. A. (New Jersey, Wiley, 2009)
Introduction to Plant Physiology became the best-selling first edition plant physiology text of the 1990's! Now, we're building on the success of prior editions to provide an even more effective fourth edition. Plant Physiology has been praised for its excellent balance of traditional and modern topics, presented in a straightforward style, without overwhelming undergraduates with excessive detail. Its focus is on the ideas and experimental approaches in plant physiology. This is a one-semester course. It assumes that the student has had introductory biology or botany as a pre-requisite.
Includes bibliographical references.; Appendix 481-487p.; Index 489-503p.
Keywords: Plants; Plants physiology; Botany